The Influence of Remote Hearing Aid Adjustment Technology on the Current Practice of Tele-Audiology among Audiologists in Malaysia - Quar, T Kar; Lim, Y Feng; Rashid, Mohd F N; Chu, S Ying; Chong, F Yen (Journal of the American Academy of Audiology, 2024)
Many hearing aid manufacturers have developed application programs that allow audiologists to fine-tune or adjust their patients' hearing aids remotely. This study aims to explore audiologists' experiences in using the remote hearing aid adjustment in Malaysia. This is a qualitative research design where focus group discussions among audiologists were held. The interview data were analyzed using reflexive thematic analysis to identify patterns and reconstruct meaning. Ten audiologists with at least 1 year of work experience in providing remote hearing aid adjustment services to adult patients were recruited. Even though there has been an increased utilization of remote fine-tuning among audiologists in Malaysia due to the coronavirus disease 2019 pandemic, its use among audiologists remains limited at present. Five thematic areas were identified: "Adoption of Practice," "Challenges and Limitations," "Benefits and Opportunities," "Satisfaction," and "Recommendations for Improvement." The TedAP challenges (T-technical challenges: e-ease of use, d-digital competency; A-abuse of system, and P-physical examinations) have been identified under the "Challenges and Limitations" theme. Suggestions for improvement include integrating the applications and video calls on a common platform, assigning a "standby" trained audiologist, and incorporating remote fine-tuning into audiology education. Challenges and limitations associated with the provision of tele-audiology have been documented based on the views and experiences of audiologists in Malaysia. Despite the barriers, audiologists acknowledged the benefits associated with remote systems and recommendations were provided to improve the services. The results of this study could contribute to the increase in the use of tele-audiology in Malaysia. This would be instrumental in developing further the audiology profession in terms of the adoption of tele-audiology and telehealth in Malaysia.